HUBUNGAN ANTARA PENGURUS PEMILIK BANK DAN KEBANGKRUTAN BANK DI INDONESIA - Ghozali, Imam; Sinaga, Dani Surya (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2006)
The objective of this research is to investigate the relationship between stocks ownership by directors and commissioner and bank bankruptcy. Sample of 34 banks were selected from 111 banks where their CEO and commissioner at the end of 1995 were also shareholders of their bank.The result shows that commissioner stock ownership was significantly related with bankruptcy. Meanwhile, CEO stock ownership shows insignificant relation with bank bankruptcy